Risk Cost-Benefit Analysis of 3 GI Angke Transformers To Achieve Optimal Mitigation - Imran Syahrizal; Budi Sudiarto (Syntax Corporation, 2022)
The power transformer is one of the leading electrical instruments used to transmit electrical power between generators to adjust the voltage without changing its frequency. Like any other machine, the power transformer will experience degradation over time. High electrical resistance, external factors and environmental temperature could lead to faster degradation. This degradation usually affects transformer isolation material. Degradation of this component furthermore will decrease power transformer efficiency. In 2022, power transformer 3 GI Angke has been used for 28 years, while PT PLN (Persero) has decided that power transformers operating for over 25 years fall into the category of the old machine and need to be replaced. The last asset wellness maintenance data showed that ethane was found in the oil insulation in the second level inspection. The third level inspection also showed degradation of bushing insulation, with the tan delta test result showing the value of 1.28. Asset wellness management is needed in this situation to ensure stability. There are two mitigation options available, to replace some of the components or replace the power transformer altogether. Risk, cost and benefit analysis using a multicriteria approach is used in choosing the best mitigation approach for PT PLN (Persero).